A regulatory gene network related to the porcine umami taste receptor (TAS1R1/TAS1R3). (11th November 2015) - Kim, J. M.; Ren, D.; Reverter, A.; Roura, E.
Summary: Taste perception plays an important role in the mediation of food choices in mammals. The first porcine taste receptor genes identified, sequenced and characterized, TAS1R1 and TAS1R3, were related to the dimeric receptor for umami taste. However, little is known about their regulatory network. The objective of this study was to unfold the genetic network involved in porcine umami taste perception. We performed a meta‐analysis of 20 gene expression studies spanning 480 porcine microarray chips and screened 328 taste‐related genes by selective mining steps among the available 12 320 genes. A porcine umami taste‐specific regulatory network was constructed based on the normalized coexpression data of the 328 genes across 27 tissues. From the network, we revealed the 'taste module' and identified a coexpression cluster for the umami taste according to the first connector with the TAS1R1 / TAS1R3 genes. Our findings identify several taste‐related regulatory genes and extend previous genetic background of porcine umami taste.